PENGARUH BAKAT DALAM PENCAPAIAN PRESTASI BELAJAR - Ahmad Badwi (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2018)
Talent is a special ability that stands out from various types of people, special abilities are usually in the form of skills or something in a field of science, such as special abilities in the fields of art, sound music, sports, mathematics, language and social religion and so on. Factors in talent development are internal factors and external factors which include; Personality factors and genetic factors, personality factors are psychological states in which the child's potential development depends on the child's self and emotions. This will help children to form concepts and be optimistic and confident in developing their interests and talents. While genetic factors are factors that support the development of individuals in talent as a totality of characteristics inherited from parents to children in all potential through psychic, which is owned by individuals from birth. The heredity factor is the first factor in the emergence of talent.